Psychotropic Drugs and Ocular Side Effects - İpek Sönmez; Ümit Aykan (Türk Oftalmoloji Dergisi)
Nowadays, the number of patients using the types of drugs in question here has significantly increased. A study carried out in relation with the long-term use of psychotropic drugs shows that the consumption of this group of drugs has substantially increased in terms of variety and quantity. In this paper, we present our review of the literature pertaining to ocular complications of psychotropic drugs in long-term treatment profile of numerous patients. If the doctor and the patients are informed about the eye problems related to the use of psychotropic drugs, potential ocular complications can be easily prevented, supervised, and controlled and can even be reversed. (Turk J Ophthalmol 2014; 44: 144-50)